Common Genetic Variants Influence Circulating Vitamin D Levels in Inflammatory Bowel Diseases. Issue 11 (November 2015) - Ananthakrishnan, Ashwin N.; Cagan, Andrew; Cai, Tianxi; Gainer, Vivian S.; Shaw, Stanley Y.; Churchill, Susanne; Karlson, Elizabeth W.; Murphy, Shawn N.; Kohane, Isaac; Liao, Katherine P.; Xavier, Ramnik J.
Abstract : Background: The accuracy and utility of electronic health record (EHR)–derived phenotypes in replicating genotype–phenotype relationships have been infrequently examined. Low circulating vitamin D levels are associated with severe outcomes in inflammatory bowel disease (IBD); however, the genetic basis for vitamin D insufficiency in this population has not been examined previously. Methods: We compared the accuracy of physician-assigned phenotypes in a large prospective IBD registry to that identified by an EHR algorithm incorporating codified and structured data. Genotyping for IBD risk alleles was performed on the Immunochip and a genetic risk score calculated and compared between EHR-defined patients and those in the registry. Additionally, 4 vitamin D risk alleles were genotyped and serum 25-hydroxy vitamin D [25(OH)D] levels compared across genotypes. Results: A total of 1131 patients captured by our EHR algorithm were also included in our prospective registry (656 Crohn's disease, 475 ulcerative colitis). The overall genetic risk score for Crohn's disease ( P = 0.13) and ulcerative colitis ( P = 0.32) was similar between EHR-defined patients and a prospective registry. Three of the 4 vitamin D risk alleles were associated with low vitamin D levels in patients with IBD and contributed an additional 3% of the variance explained. Vitamin D genetic risk score did not predict normalization of vitamin D levels. Conclusions: EHR cohorts form valuable data sources for examining genotype–phenotype relationships. Vitamin D risk alleles explain 3% of the variance in vitamin D levels in patients with IBD. Abstract : Article first published online 1 August 2015.Supplemental Digital Content is Available in the Text.